The Impact of Environmental Work Conditions on the Performance of Employees in Private Lebanese Hospitals During the Lebanese Financial Crisis: A Case Study of Private Hospitals in Northern Lebanon (Entrepreneurship Journal for Finance and Business, 2023)
The aim of this research is to determine the effect of work environment conditions on the performance of workers in Lebanese private hospitals in North Lebanon during the Lebanese financial crisis. A sample of 95 employees of various positions in private hospitals located in North Lebanon was studied: Al-Shamal Hospital, Moawad Hospital, Saydet Hospital, North Lebanon. The descriptive analytical approach was chosen for this research. The data was analyzed using the SPSS statistical program, and descriptive and analytical statistics were used in the analysis process. The results showed that there is a direct, statistically significant effect of the physical and behavioral conditions of the work environment on the health of workers in private hospitals in northern Lebanon during the financial crisis in Lebanon. There is also a direct, statistically significant effect of the health of employees at work on their performance in private hospitals in northern Lebanon during the financial crisis in Lebanon.